The Effect of Self-Efficacy and Interest on Career Decisions with Achievement Motivation as a Mediating Variable on Generation Z in Surakarta - Haliza, Muthiara Nur; Irmawati, Irmawati (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the influence of self-efficacy and interest on career decisions of Generation Z in Surakarta, with achievement motivation as a mediating variable. Using quantitative methods with SmartPLS analysis, this study involved 100 Generation Z respondents. The results showed that self-efficacy had a significant positive effect on career decisions, while interest had no direct effect. Achievement motivation was shown to mediate the relationship between self-efficacy and interest on career decisions. These findings emphasize the importance of strengthening self-efficacy and achievement motivation so that Generation Z can make appropriate career decisions.